Perbandingan Tema dan Gaya Dalam Syair Melayu Riau dan Syair Melayu Lainnya - Melani Putri; Muhammad Akbar; Nur’almaydaniati Hamid; Riska Sari Putri; Wilidia Nanda Agustina; Herlinda Herlinda (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
Poetry is one of the old literary genres that developed in the archipelago, including in the Malay region of Riau. This study aims to analyze and compare the themes and writing styles contained in Riau Malay poems with Malay poems from other regions. Using a content analysis approach, this study examines a number of Riau Malay poetry and Malay poetry from other regions to explore the themes raised and the writing style used. The results of the study show that Riau Malay poetry and other Malay poetry have similarities in raising certain themes such as advice, heroic stories, and love. However, there are differences in the emphasis on themes and the use of language styles. Riau Malay poetry tends to emphasize more on the aspect of Islamic advice and values, while other Malay poetry explores more themes of love and heroism. In terms of writing style, Riau Malay poems tend to use a simpler and more understandable language, while other Malay poems often use a more poetic and metaphorical language style. This research contributes to enriching the understanding of the richness of the archipelago's old literary treasures, especially Malay poetry, as well as the differences and uniqueness of poems from various regions.